2010
DOI: 10.1016/j.joca.2010.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Assessing degeneration of human articular cartilage with ultra-short echo time (UTE) T2* mapping

Abstract: Objective To examine the sensitivity of ultra-short echo time (UTE) T2* mapping to collagen matrix degeneration in human articular cartilage. Methods MRI UTE-T2* maps and standard T2 maps were acquired on four human tibial plateau explants. Thirty-three osteochondral cores were harvested for polarized light microscopy (PLM), and composition analyses. Collagen matrix integrity was evaluated from PLM and histological images. Matrix integrity and composition was compared to standard T2 values and UTE-T2* values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
173
0
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(187 citation statements)
references
References 37 publications
11
173
0
3
Order By: Relevance
“…Quantitative MRI (qMRI), with its ability to quantify tissue relaxation times, presents an objective measure of collagen organization. Current qMRI techniques such as T2* mapping for articular cartilage cannot capture the very short T2 values of meniscal fibrocartilage [10]. T2* mapping using an ultrashort echo time (UTE) pulse sequence acquires short echo images (echo time (TE) ∼0.3 ms) to produce multi-echo images for quantitative T2* calculation [2].…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative MRI (qMRI), with its ability to quantify tissue relaxation times, presents an objective measure of collagen organization. Current qMRI techniques such as T2* mapping for articular cartilage cannot capture the very short T2 values of meniscal fibrocartilage [10]. T2* mapping using an ultrashort echo time (UTE) pulse sequence acquires short echo images (echo time (TE) ∼0.3 ms) to produce multi-echo images for quantitative T2* calculation [2].…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative strategies for the diagnosis and staging of joint tissue degeneration prior to the breakdown of the articular cartilage or meniscal surfaces remain a challenge. Our research has shown that the current clinical standard, arthroscopic visualization, and palpation of cartilage and menisci, may be insensitive to early subsurface alterations in these tissues, particularly in the deepest layers of articular cartilage [1][2][3]. Our work with quantitative Magnetic Resonance Imaging (MRI) and Optical Coherence Tomography (OCT) reveals a strong potential for these methods to provide information regarding early diagnosis and staging of subsurface tissue injury that are not readily available with current technologies [3][4][5].…”
Section: Introductionmentioning
confidence: 94%
“…MRI ultra-short TE-enhanced T2* (UTE-T2*) mapping reflects the cartilage collagen matrix integrity as determined by polarized light microscopy and is sensitive to signal from the deepest layers of cartilage adjacent to bone [2,3]. UTE-T2* mapping of articular cartilage and meniscus has the potential to visualize deep tissue characteristics better than standard T2 mapping due to its sensitivity to signal from short T2 tissues.…”
Section: Quantitative Imaging Of Articular Cartilagementioning
confidence: 99%
“…Recently, ultrashort echo time enhanced T2* (UTE-T2*) mapping was developed to evaluate the subsurface matrix of articular cartilage 10,11 (Fig. 2).…”
Section: Early Diagnosis Enables Early Treatment To Reduce Osteoarthrmentioning
confidence: 99%